Functional and microvascular anatomy of the ocular bulb in wild pig: a scanning electron microscopic study - Takci, Lutfi; Kurtul, Ibrahim; Yilmaz, Sadik (Tubitak Scientific & Technological Research Council Turkey, 2021)
This study searched the functional, macro- and microvascular anatomy of the ocular bulb in the 20 wild pigs to evaluate the effects of domestication on the eye comparatively by applying macroanatomical dissection techniques, Crossmon's modified triple staining technique, and scanning electron microscopy (SEM) through corrosion cast technique. The ocular bulb was vascularized by the internal ophthalmic artery along with the external ophthalmic artery. Erythrocytes were observed in the capillaries of the inner layers of the retina. Distinctive functional adaptations were documented in the microvasculature of the ocular components, such as the marginal capillaries with irregular enlargements and narrowings following parallelly running and markedly convolute courses and ending with pinpoint-like terminations in the ciliary body. The iridal arterioles run a zigzag pathway, forming coherent undulations each other, and ending as bud-like structures, which seem to be artifacts due to incomplete filling of the resin. These peculiarities contribute probably to the compensation in capillary pressure.
Keywords: Ocular bulb; corrosion cast; scanning electron microscopy (SEM); wild pig; vascularisation